Ecological Protection Technology of Spraying Vegetation Concrete on Carbonaceous Rock Slope Experimental Research and Application. (25th February 2022) - Chang, Zhenchao; Luo, Junhui; Tang, Qiongzhen; Zeng, Ling; Zhang, Hongri; Li, Youjun; Yang, Gexiao; Zhang, Liming
Abstract : To solve the environmental protection issue of carbonaceous rock slope, the failure mechanism of carbonaceous rock slope and the protection mechanism of vegetation concrete are analyzed based on the engineering characteristics of carbonaceous rock and vegetation concrete. Therefore, the field test of vegetation concrete was carried out to obtain the optimal dosage of vegetation concrete greening additive. The application of environmental protection technology of vegetation concrete on carbonaceous rock slope is applied in slope engineering of Hebai highway, and the change law of soil fertility was analyzed to verify the effect of ecological protection. The results show that the protection mechanism of vegetation concrete slope protection technology is mainly categorized into two groups, namely, the surface sealing effect of vegetation concrete substrate in the early stage and the plant ecological protection effect in the later stage. The experiment results show that the optimum dosage of green additive for vegetation concrete is ranging from 30 kg/m 3 to 40 kg/m 3 . According to the field application, within one year after the construction of vegetation concrete, the contents of available phosphorus, potassium, and organic matter increased by 70.2%, 24.9%, and 76.8%, respectively. Moreover, the content of alkali hydrolyzed nitrogen decreased by 44.8% and bulk density by 17.4%; the content of total phosphorus changed little. After 60 days of construction, the vegetation coverage rate of the slope can reach more than 95% and there is no obvious soil erosion phenomenon after three times of heavy rainfall.